2009
DOI: 10.1002/art.24493
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diagnostic utility of spinal magnetic resonance imaging in axial spondylarthritis

Abstract: Objective. Magnetic resonance imaging (MRI) is increasingly used for the diagnosis of axial spondylarthritis (SpA), but it is unknown whether characteristic lesions are actually specific for SpA. This study was undertaken to compare MRI patterns of disease in active SpA, degenerative arthritis (DA), and malignancy.Methods. Fat-suppressed MRI of the axial skeleton was performed on 174 patients with back pain and 11 control subjects. Lesions detected by MRI, including Romanus lesions (RLs) and end-plate, diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 34 publications
6
83
0
2
Order By: Relevance
“…However, the reader was asked to ignore BME lesions if typical of spondylosis, and there was no association between the presence of severe IVD lesions and fulfillment of ASAS spine criteria. This finding is consistent with a previous study, which showed that inflammatory changes in axial SpA or spondylosis were not influenced by the presence of IVD lesions and were specific of axial SpA only in the younger subset of patients (ages ≤50 years) (37). Thus, the influence of disc degeneration on spinal inflammatory changes might be limited.…”
Section: Discussionsupporting
confidence: 92%
“…However, the reader was asked to ignore BME lesions if typical of spondylosis, and there was no association between the presence of severe IVD lesions and fulfillment of ASAS spine criteria. This finding is consistent with a previous study, which showed that inflammatory changes in axial SpA or spondylosis were not influenced by the presence of IVD lesions and were specific of axial SpA only in the younger subset of patients (ages ≤50 years) (37). Thus, the influence of disc degeneration on spinal inflammatory changes might be limited.…”
Section: Discussionsupporting
confidence: 92%
“…Correlations between MRI lesions and disease activity in Italian axSpA patients of injury most frequently observed in axSpA is BME of the anterior vertebral corners, which is an expression of anterior osteitis (19). Another type of lesion that is detected is the replacement of vertebral angles with adipose tissue (fatty lesions), which seems to be less specific and occur later in SpA (23,24). The presence of BME at the posterior vertebral corners appears to be highly specific for this disease, but its use as a diagnostic criterion has been limited by low sensitivity.…”
Section: N Discussionmentioning
confidence: 99%
“…The group of patients who developed hand OA also had a higher GUESS score. This is noteworthy because degenerative arthritis of the DIP joint and spine as determined by magnetic resonance imaging (MRI) is associated with entheseal abnormalities 10,11 ; indeed there is good evidence that OA of small joints of the hand has a ligament-related microanatomical basis similar to entheseal PsA 12 . Moreover, it may be difficult to distinguish between OA and PsA, as both may affect the DIP joint and the axial skeleton and may show similar entheseal changes on MRI 10 .…”
Section: Rheumatologymentioning
confidence: 99%